MENINJAU JAMINAN KECELAKAAN DILUAR JAM KERJA BERDASARKAN PERDA KABUPATEN KARAWANG NOMOR 1 TAHUN 2011 - Widia Sari; Imam Budi Santoso (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The Employment Social Security Administering Agency provides protection for workers to overcome certain risks and implements them using social insurance mechanisms. What is meant by labor guarantees outside of working hours in the Karawang Regency Regional Regulation No. 1 of 2011? what are the provisions regarding work accidents outside of working hours?, Data Research Methods and Data Sources. Primary legal materials are regulations related to the Karawang regency regulation no. 1 of 2011. Secondary legal materials are books and opinions of experts in various literatures. Tertiary Law materials, such as the Big Indonesian Dictionary, scientific articles. Drawing conclusions. Accidents outside working hours are accidents that occur after working hours are over, in Law No. 3 of 1992 concerning Labor Social Security, work accidents include accidents when going home and going to work. other conditions that can be categorized as work accidents (outside working hours, excursions, etc.)The provisions regarding work accidents outside of working hours, namely the social security of workers intended for workers, social security of workers also applies to families of workers. Workers who are affected by work accidents are entitled to receive Work Accident Insurance.Key words: Accidents, labor and working hours.